Empirical Research for Information Professionals - Liu, Yan Quan (Createspace, 2019)
A collection of empirical research published by Dr. yan Quan Liu and his reasearch teams in the field of information and library science for the 21st-century readers. - Back cover.
Keywords: Case studies; Library science; Research; Library science; dept.ils; faculty_collection

The Enlightenment of Pew Research Center's Information Management Practice on Academic Library Think Tank Services / 皮尤研究中心信息管理实践对学术图书馆智库服务的启示 - Liang, X.; Liu, Yan Quan (Library & Information, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Investigation and Research on the Application of Artificial Intelligence Technology in Library Service / 图书馆服务中人工智能技术应用的调查研究 - Yang, Z.; Wang, Y.; Liu, Yan Quan; Qu, Z. (Library/TU Shu Guan, 2019)
Keywords: dept.ils; ⛔ No DOI found

Public Libraries and the Opioid Crisis, Part 1: Context and Commitment - Real, Brian; Bogel, Gayle (Public Library Quarterly, 2019)
Public libraries have been significantly affected by the opioid crisis. The fact that patrons can enter libraries freely and do not need a reason to be there has resulted in overdoses occurring in many such buildings throughout the country. In response to this, library directors have developed plans of action that, in some cases, include training librarians to administer the opioid overdose reversal drug Naloxone. This present article – the first in a two-part study – is based on interviews with representatives from libraries that have been significantly affected by the opioid crisis. After describing these community circumstances, the authors analyze various ways that each library has prepared to respond to overdoses and other emergency situations.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/172-972-683-218-803, pop00020 tex.type: [object Object]
Keywords: Narcan; Public libraries; dept.ils; opioid dependency; opioids; peer-reviewed

Public Libraries and the Opioid Crisis, Part 2: Community-Centered Responses - Real, Brian; Bogel, Gayle (Public Library Quarterly, 2019)
Numerous articles from major national newspapers have covered the fact that as the opioid crisis has become a pervasive problem in the United States, overdoses in public libraries have become a somewhat common occurrence. Many of these discussions center on librarians being trained to use the overdose reversal drug Naloxone, and that was the primary focus of the first part of this two-part study. However, this second article discusses what libraries are doing to mitigate the impacts of the crisis and help persons from vulnerable populations before matters escalate to become emergency situations. The authors document how libraries are attempting to educate their communities about the opioid crisis, ways they have partnered with community organizations to help opioid dependent persons, and how they have addressed various facilities and security concerns for their buildings.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/040-002-193-003-128, pop00139 tex.type: [object Object]
Keywords: Public libraries; dept.ils; facilities management; opioids; peer-reviewed; security; vulnerable populations

Confronting librarianship and its function in the structure of white supremacy and the ethno state - Sierpe, Eino (Journal of Radical Librarianship, 2019)
Rising socio-cultural and political tensions have helped increase awareness about long-standing structures of violence and abuse, as we have seen in the development and tumultuous expansion of the #MeToo movement. However, other significant conditions of injustice and oppression continue without drawing attention. This seems to be the case with the library profession. Despite strong and persistent links to white supremacy and a well-established record excluding minorities from its ranks, the library profession has been remarkably successful in nurturing an unassailable public image of virtuous liberal benevolence and near mythical devotion to the highest ideals of freedom, individual rights, and democracy. Its unsurpassed ability in evading scrutiny or criticism of any serious consequence while maintaining a strong record of dedicated service to white power is all the more remarkable at a time where social media is used to amplify campaigns against injustices or organizations believed responsible for conditions of oppression. Although Critical Librarianship, or #CritLib, is beginning to question some of the doctrinal assumptions underlying the practice of librarianship, an examination of some of the mechanisms with which white supremacy has been able to build an entire system of racial protectionism as an occupational sector that intersects with areas of significant public interest is an important and timely research concern.
Citation Key Alias: lens.org/069-727-951-165-240, pop00317
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Are urban public libraries websites accessible to Americans with Disabilities? - Liu, Yan Quan; Bielefield, Arlene; McKay, Peter (Universal Access in the Information Society, 2019)
This paper examines to what extent the 129 members of the Urban Public Libraries Council meet the Section 508 standards for accessibility under the Rehabilitation Act, the minimum acceptable standard for accessibility under the Americans with Disabilities Act. Using an HTML evaluation tool, WAVE, the HTML coding of the libraries’ homepages was evaluated according to the Section 508 criteria for accessibility. After one-to-one deep examination to determine the accessibility of the library websites, the results tended to mirror other studies showing that most library websites have some coding deficiencies that limit the accessibility of the websites. Notably, only 7 of the 122 libraries that were surveyed had no Section 508 errors present with their homepages.
7 citations (Crossref) [2023-10-31] tex.ids: ISI:000461373700014, lens.org/058-290-057-137-474, liuAreUrbanPublic2019 tex.address: [object Object] tex.affiliation: [object Object] tex.author-email: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: ADA; Accessibility; Assistive technology; Compliance; Disability; HTML; Impairment; Libraries; Policy; Public libraries; Public library; Public policy; Section 508; Section508; Section 508; Universal usability; Urban libraries; Websites; dept.ils; peer-reviewed

An Analytical Study of Recommendation Systems in Chinese City Libraries / 城市图书馆馆藏资源推荐系统调查分析 - Guo, Q; Liu, Yan Quan; Wang, Y (Research on Library Science, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Differences, Complementarity and Convergence of University Library Mobile Service Platforms / 高校图书馆移动服务平台的差异、互补与融合 - Liu, Yan Quan; Zhao, F (Journal of the National Library of China, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

The Model and Challenges of Volunteer Service Mechanism in American Urban Libraries / 美国城市图书馆志愿者服务机制模式及面临的挑战 - Ren, X; Liu, Yan Quan (Library & Information, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found